Short-term effects of selective transcutaneous auricular-nerve stimulation measured in a subject with angina pectoris - Rozman, Janez (Materiali in tehnologije, 2021)
We have measured the short-term effects of selective, transcutaneous, auricular-nerve stimulation (tANS) on the heart function, respiratory function, thermal function and galvanic skin response in a patient with angina pectoris with respect to four predefined sites on the left and right cymba concae (CC). The tANS involved the use of a train of monopolar, current, biphasic pulses composed of rectangular cathodic ic and anodic phases ia and globule-like platinum stimulating electrodes. The parameters of the stimulating pulses were as follows: frequency f = 45.5 Hz, cathodic phase width tc = 200 micros, anodic phase width ta = 200 micros, interphase delay d =180 micros, pulse-train duration 2.0 s and time gap between pulse trains 1.0 s. The results show that tANS at predefined sites on the CC produce measurable effects on the assessed vital functions. In conclusion, tANS witbih an increased number of channels, has the potential to be used in the treatment of certain disorders.
Keywords: angina pektoris; elektrostimulacija; external ear; platinske elektrode; platinum electrodes; transcutaneous auricular-nerve stimulation; transkutana stimulacija ušesnega živca; zunanje uho